Effects of Different Levels of Flea Infestation on Gut Microbiota of Brandt’s Voles (Lasiopodomys brandtii) in China - Zhenxu Wang; Lu Wang; Chenran Guo; Zihao Wang; Xinchang Lun; Haoqiang Ji; Meng Shang; Xiaoxu Wang; Qiyong Liu (Animals)
Brandt’s vole is a common small rodent, and its gut microbiota is critical to host health and immune function. The parasitic fleas commonly found in Brandt’s voles cause an immune response, but their impact on the gut microbiota remains unclear. According to the level of flea infestation, Brandt’s voles were divided into the control group, low-infestation group, and high-infestation group. The changes in the microbial community composition, abundance, and diversity of the gut microbiota were evaluated using 16S rRNA sequencing. Flea infestation significantly affected body weight, food intake, and gut microbiota structure. The low-infestation group exhibited the most pronounced changes in weight and food intake, while the high-infestation group showed the least. In the 4th week, 16S rRNA sequencing revealed an increase in alpha diversity and alterations in microbial composition. Beta-diversity analysis indicated significant differences in the intestinal microbiota between the experimental groups and the control group. By the 8th week, these differences had diminished, suggesting that the microbiota had stabilized or recovered over time. Overall, parasitic flea infestation significantly alters the diversity, structure, and characteristic microbial enrichment of the gut microbiota in Brandt’s voles, potentially impacting host metabolism, immunity, and growth. While this study lasted 8 weeks, the long-term health effects of flea infestation may persist. Future research should elucidate the interaction mechanisms between parasites and hosts, define the time frames and mechanisms of these long-term impacts, and provide theoretical support for animal health management and disease control.